Paediatric oncology in the developing world: An African perspective. - Nkrumah, F.K. (Annals of Tropical Paediatrics, 1987)
Nutritional deficiency and infectious diseases constitute major paediatric priorities in most developing countries in Africa today. It is suggested that successful implementation of the various cost-effective intervention programmes which address themselves to these priorities will gradually unveil other paediatric problems presently considered of low priority. These will include the malignant diseases of childhood. The very high cost of cancer detection and treatment will demand carefully reasoned and planned approaches in most Third World countries. The implications of this in relation to childhood malignancies in Africa are discussed.